2017
DOI: 10.1074/jbc.ra117.000184
|View full text |Cite
|
Sign up to set email alerts
|

The KLF14 transcription factor regulates hepatic gluconeogenesis in mice

Abstract: Krüppel-like factor 14 (KLF14) is a member of the Cys/His zinc-finger DNA-binding proteins. Despite strong evidence showing that a polymorphism in the gene is closely linked to the development of type 2 diabetes, the physiological and metabolic functions of KLF14 still remain unclear. In the present study, we investigated the role of KLF14 in the regulation of hepatic gluconeogenesis. Adenoviruses expressing KLF14 (Ad-) or KLF14-specific shRNAs (Ad-sh) were injected into normal C57BL/6J, diabetic, or high-fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 33 publications
2
23
1
Order By: Relevance
“…The first of these genes, Klf14 , encodes the maternally expressed Krüppel-like factor 14 (Klf14), a member of the Cys2/His2 zinc finger transcription factors ( Small et al. 2011 ; Wang et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these genes, Klf14 , encodes the maternally expressed Krüppel-like factor 14 (Klf14), a member of the Cys2/His2 zinc finger transcription factors ( Small et al. 2011 ; Wang et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…2011 ), and may be involved in metabolic disease risk. In addition, recent results in mice suggest that Klf14 may interact with peroxisome proliferator-activated coactivator ( ), a transcription coactivator that regulates a number of metabolic pathways, including hepatic gluconeogenesis ( Wang et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Argmann et al showed that mice harboring whole-body germ-line deletion of Klf14 were resilient to HFD-induced insulin resistance (91). Their results were inconsistent with the previously reported role of KLF14 in regulating HDL-C levels in the liver (92,93). This is possibly due to the utilization of different mouse lines ( Table 2).…”
Section: The Role Of Klf14 In Adipose Tissuementioning
confidence: 87%
“…It has been shown that hepatic KLF14 regulates glucose production in fasted and re-fed mice as well as diet-induced and genetically obese mice (93). Several lines of evidence suggest that increased KLF14 expression facilitates gluconeogenesis (93).…”
Section: The Role Of Klf14 In Liver Tissuementioning
confidence: 99%
“…promote gluconeogenesis through increasing the transcription of the rate-limiting enzyme for gluconeogenesis, PEPCK (10). Additionally, each of these factors does so via regulation of PGC1α transcription or activity ( Figure 1B): KLF9, KLF10, and KLF14 increase Pgc1a transcription, and KLF15 binds to and cooperates with PGC1α on the Pepck promoter (18)(19)(20).…”
Section: The Klfs Coordinate Interorgan Metabolic Crosstalkmentioning
confidence: 99%